Analisis Pengaruh Pengetahuan Ibu Terhadap Waktu Pemberian Mp-Asi Pada Anak Usia 6-24 Bulan - Wendy Kayrani Wafiq (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
Complementary food for ASI (MP-ASI) is food or drink that contains nutrients, which is given to infants to meet nutritional needs other than breast milk. Complementary food for breastfeeding given to infants must contain sufficient micronutrients to meet needs that are not met by breast milk alone. But until now the provision of MP-ASI to babies less than 6 months in Indonesia is still a health problem that needs attention, because there are still many mothers who give solid food to babies before the baby is 6 months old (Heryanto, 2017). According to the World Health Organization (WHO) in 2017, only about 40% of babies aged 0-6 months worldwide are exclusively breastfed, while 60% of other babies have received MP-ASI when they are less than 6 months old. This illustrates that exclusive breastfeeding is still low, while the practice of giving MP-ASI in various countries is still high. The data based on the 2018 Basic Health Research (RISKESDAS) shows 37.3% of babies aged 0-5 months get exclusive breastfeeding, 9.3% get partial breastfeeding and 3.3% get predominant breastfeeding. Predominant breastfeeding is a pattern of breastfeeding where the baby besides getting breast milk is also given a little water. Partial breastfeeding is a pattern of breastfeeding where the baby besides getting breast milk is also given artificial food such as formula milk, porridge or other food before the baby is exactly 6 months old which is given continuously or always given breast milk (prelacteal). The prelacteal food most often given to newborns is formula milk (79.8%) (Ministry of Health RI, 2018).